Предмет: Алгебра,
автор: артёмка322
Помогите пожалуйста!
1 Упростите выражение 3x(3x²+1)-(x-3)(x+3)-5x²
2 Разложить на множетели (a-b)²+3a-3
3 Решить уравнение 5y²-2y=0
4 Выполнить умножение(3a-b)(2b+4a)
5 Преобразовать в многочлен (4y-5x)²
Ответы
Автор ответа:
0
1. 3x(3x²+1)-(x-3)(x+3)-5x²=9x³+3x-(x²-9)-5x=9x³+3x-x²+9-5x=8x+9+9x³+x²
Похожие вопросы
Предмет: Алгебра,
автор: Аноним
Предмет: Физика,
автор: sahnozam751
Предмет: География,
автор: foksitvlolyyyyoooo
Предмет: Литература,
автор: xanu9603xany